Respostas da vegetação de cerrado às mudanças climáticas e atividades antrópicas no nordeste do Brasil durante o holoceno tardio - Xavier, Sérgio Augusto Santos (2023)
In the upcoming decades, the Cerrado (Brazilian savanna) is expected to undergo structuralchanges and altered natural dynamics due to the ongoing global warming and humanpressures. In this context, palaeoecological studies allow the reconstruction of past landscapeswhen they were subjected to different climatic conditions and other agricultural practices. Theaim of this thesis is to study and understand the interactions between vegetation, climatechange and fire regimens during the last 6000 years in the Cerrado of Northeastern Brazil(NEB). Multiproxy analyses (pollen and charcoal) were carried out in two sediment cores,SAC18 was collected in Sete Cidades National Park, North of Piauí State, and core VDD-13was collected in Chapada das Mesas National Park, Southwest of Maranhão State. At SeteCidades, open vegetation dominated from 1200 to 1350 CE. Natural fires occurred at thetransition from dry to wetter phase around 1350-1400 CE. Then, from 1400 CE onwards, awoody cerrado and palm swamp expanded when the Intertropical Convergence Zone shiftedsouthward. Three different land use practices were observed: Amerindians between 1400 and1650 CE, Europeans between 1650 and 1960 CE and conservation policy from 1961 CEonwards, which mitigated deforestation and fires. At Chapada das Mesas, open vegetationdominated during a dry phase from 6000 to 5200 cal yr BP, when the monsoon convectionwas weakened. Then, a woody cerrado and palm swamp during a moister phase expandedfrom 5200 to 4300 cal yr BP, when the monsoon moisture strengthened. Almost no fire wasobserved, which can be attributed to the lower fuel availability during the dry phase and thewet biomass during the moister phase. Nine sterile samples characterized a strong dry periodaround 4200 cal yr BP which lasted until 3600 cal yr BP. Reorganization of dry resistant taxaand moisture related taxa indicated increasing humidity to a seasonal climate, with constantfires until 2600 cal yr BP. Then, fires stopped and the expansion of woody cerrado, palmswamp and gallery forest marked the onset of a wet period, when the monsoon intensified inthe west. This palaeoecological reconstruction, based on the results of this thesis and otherrecords, sheds new light on the regional climate of NEB during the last 6000 years. Between6000 and 5200 cal yr BP, an open vegetation in the western attested dry conditions caused byweakened monsoon convection on the Amazon basin. Between 5200 and 4200 cal yr BP, theexpansion of woody cerrado and amazon rainforest taxa on western NEB and palm swampand tree taxa in eastern NEB, reflected higher moisture rates all over the region. After 4200cal yr BP, the development of Caatinga in the east attested the installation of a dry climate,while the expansion of the Amazon rainforest and Cerrado in the west reflected thestrengthened monsoon. Natural fires occurred mostly in eastern NEB between 6000-4200 calyr BP. Since 3000 cal yr BP, the intensification of human activities in the region ischaracterized by an increase in fire activity under dry and wet conditions. During the last6000 years, the vegetation in the west was more sensitive to the monsoon variability and inthe east more sensitive to the ITCZ shifts and Sea Surface Temperature (SST). Anthropogenicactivity in NEB was stronger after 3000 cal yr BP, when native groups spread across theregion. Consequently, the history of fire regimen in NEB was a combination of naturaldynamics between vegetation and climate during the mid-late Holocene and humanenvironment interactions during the late Holocene. Today predictions show that monsoon shiftto the south and SST increase could lead to rainfall depletion and warmer temperatures overNEB, causing reduction of regional vegetation cover in both eastern and western NEB andbiodiversity loss.